HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PASIEN HIPERTENSI - I Gede Purnawinadi; Irene Jessica Lintang (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2020)
ABSTRACT Introduction: Hypertension requires lifelong treatment. One influence of the successful treatment of hypertensive patients is adherence to taking drugs through family support roles. Purpose: This study identified the relationship between family support and adherence to taking medication for hypertensive patients at the Airmadidi Health Center in North Minahasa Regency. Method: This study was an observational analytic with cross-sectional approach. The sampling technique used was purposive sampling with a sample of 127 respondents diagnosed with hypertension. Results: Dominant family support (84.3%) was included in the low category, and dominant medication adherence (65.4%) was included in the low category. There is a significant relationship between family support and medication adherence to hypertensive patients (p value 0.016), but the correlation coefficient is weak (r = -0.213) with a negative relationship direction. Discussion: Communities including families of hypertensive patients are expected to take part in improving compliance with taking medication for hypertensive patients, and for hypertensive patients must be more obedient in taking drugs. Keywords: Family Support, Hypertension, Adherence, Taking Medication.